2005
DOI: 10.1002/ps.1084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorpyrifos in freshwater model ecosystems: the influence of experimental conditions on ecotoxicological thresholds

Abstract: Three experiments were conducted to determine the impact of the insecticide chlorpyrifos (single applications of 0.01 to 10 microg AI litre(-1)) in plankton-dominated nutrient-rich microcosms. The microcosms (water volume approximately 14 litres) were established in the laboratory under temperature, light regimes and nutrient levels that simulated cool 'temperate' and warm 'Mediterranean' environmental conditions. The fate of chlorpyrifos in the water column was monitored and the effects on zooplankton, phytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 24 publications
(20 reference statements)
10
53
0
Order By: Relevance
“…Since the publication of the Giesy et al review, results of several cosm studies of CPY have featured prominently in comparisons of cosm studies, single-species laboratory toxicity tests, and regulatory benchmarks across classes of insecticides (Brock et al 2000(Brock et al , 2006Maltby et al 2005 ;van Wijngaarden et al 2005b ). Several newer cosm studies have broadened the scope of conclusions about chlorpyrifos effects on aquatic communities to a wider range of locations and environmental conditions (Daam et al 2008a , b ;López-Mancisidor et al 2008a , b ;van Wijngaarden et al 2005a ;Zafar et al 2011 ). The body of evidence from cosm studies is consistent in supporting the conclusion that concentrations of 0.1 μg CPY L −1 or less cause no ecologically signifi cant effects on aquatic communities.…”
Section: Evidence From Microcosms and Mesocosmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the Giesy et al review, results of several cosm studies of CPY have featured prominently in comparisons of cosm studies, single-species laboratory toxicity tests, and regulatory benchmarks across classes of insecticides (Brock et al 2000(Brock et al , 2006Maltby et al 2005 ;van Wijngaarden et al 2005b ). Several newer cosm studies have broadened the scope of conclusions about chlorpyrifos effects on aquatic communities to a wider range of locations and environmental conditions (Daam et al 2008a , b ;López-Mancisidor et al 2008a , b ;van Wijngaarden et al 2005a ;Zafar et al 2011 ). The body of evidence from cosm studies is consistent in supporting the conclusion that concentrations of 0.1 μg CPY L −1 or less cause no ecologically signifi cant effects on aquatic communities.…”
Section: Evidence From Microcosms and Mesocosmsmentioning
confidence: 99%
“…Indoor, plankton-dominated microcosms were used to compare the responses of aquatic communities to CPY under conditions pertaining to Mediterranean regions (higher temperature and greater amounts of nutrients) with conditions representing cool temperate regions (van Wijngaarden et al 2005a ). CPY was applied once to give concentrations from 0.01 to 10 μg L −1 in water of microcosms.…”
Section: Evidence From Microcosms and Mesocosmsmentioning
confidence: 99%
“…The effects can be measured in a general way and modelled with varying degrees of uncertainty (Johnes et al 1996;Van den Brink et al 2002;Bowes et al 2005;Westra et al 2005;Van Wijngarden et al 2005), but the sort of precision demanded by legislators and lobbies will never be attainable and this has been a major weapon used to delay regulation of agricultural activities.…”
Section: Problems In Relating Agricultural Activities To Environmentamentioning
confidence: 99%
“…The number of zooplankton taxa observed in the cyprodinil mesocosm experiment (49 taxa) is in the upper end of the range of the number of zooplankton taxa observed in the various micro/mesocosm experiments performed (without fish) at Wageningen University and Research Centre (25 -50 taxa; see e.g. Van den Brink et al, 1996, andVan Wijngaarden et al, 2005a). In addition, the numbers of micro-crustacean taxa in the cyprodinil mesocosm study (13 taxa) fall within the range of the number of micro-crustacean taxa observed in these studies performed in Wageningen (11-20 taxa).…”
Section: Criteria For a Suitable (Semi-)field Studymentioning
confidence: 91%